2020
DOI: 10.1093/hropen/hoaa029
|View full text |Cite
|
Sign up to set email alerts
|

Towards more patient-centred endometriosis care: a cross-sectional survey using the ENDOCARE questionnaire

Abstract: STUDY QUESTION What is the performance of the patient-centredness of endometriosis care in a secondary and a tertiary care setting and how can it be improved? SUMMARY ANSWER Overall, patient-centredness was comparable in the two endometriosis care centres, but differed regarding ‘physical comfort’ and ‘continuity and transition’; both centres can learn how to improve several of their targets from the other’s strengths. … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
18
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(22 citation statements)
references
References 20 publications
3
18
1
Order By: Relevance
“…A few studies have used ECQ previously [20, 21, 28, 29], but comparable data are only presented by Schreurs et al [30]. They reported a higher overall PCS, median 4.8 for a secondary care center, and median 4.5 for a tertiary care center [30], compared with our median 3.6. The low PCS suggests a need to strengthen PCEC, and ECQ may be used for designing and evaluating improvement projects.…”
Section: Discussionsupporting
confidence: 83%
See 1 more Smart Citation
“…A few studies have used ECQ previously [20, 21, 28, 29], but comparable data are only presented by Schreurs et al [30]. They reported a higher overall PCS, median 4.8 for a secondary care center, and median 4.5 for a tertiary care center [30], compared with our median 3.6. The low PCS suggests a need to strengthen PCEC, and ECQ may be used for designing and evaluating improvement projects.…”
Section: Discussionsupporting
confidence: 83%
“…The low PCS suggests a need to strengthen PCEC, and ECQ may be used for designing and evaluating improvement projects. ECQ may also enable more research on the determination of specific patient characteristics that may have critical effects on the outcome of PCEC [30]. The properties of ECQ enable measurements of patient centeredness both at clinical and national levels, depending on the aim of the study [21].…”
Section: Discussionmentioning
confidence: 99%
“…In the past, women with endometriosis reported that the following aspects of care could be improved: (1) health-care providers’ lack of essential knowledge, (2) inconsistent advice and, (3) the feeling of not being taken seriously [16, 30-33]. Moreover, 3 corresponding targets for improvement of patient-centred endometriosis care were found in 4 endometriosis clinics in Belgium and the Netherlands: (i) receiving practical information and advice on self-care after surgery, (ii) receiving information on pain medication, and (iii) personal follow-up by the treating physician [15, 16]. These targets for improvement are acknowledged by health-care providers, and a desire for individualized, multidisciplinary care is presented [12, 30, 34].…”
Section: Discussionmentioning
confidence: 99%
“…The ECQ is a validated questionnaire that investigates patient-centredness per endometriosis clinic by questioning women with endometriosis on performance and importance of different care aspects associated with patient-centredness. In recent years, this questionnaire has been used in various Dutch-speaking endometriosis patient populations and has shown to be a valuable tool in investigating patient-centredness of endometriosis care [15, 16].…”
Section: Introductionmentioning
confidence: 99%
“…The outcomes are converted to scores ranging 0-100 for each category. The patient-centeredness scores from the same university hospital obtained by Schreurs et al are used as a reference population (Schreurs et al, 2020).…”
Section: Questionnairesmentioning
confidence: 99%